IMPROVING THE DURABILITY OF CULTIVATOR BLADES USING ONE-SIDED GAS-FLAME SURFACING - Fayurshin, Azamat; Farkhshatov, Mars; Saifullin, Rinat; Islamov, Linar; Gaskarov, Ilnar; Masyagutov, Rivaz; Bagautdinova, Ilnara (Journal of Applied Engineering Science, 2020)
In agar production one of the most common technological operations is cutting of soil or plants. It makes up at least 70% of the total volume of mechanized works. The purpose of this study is to help maintain the agrotechnological parameters of the cultivator’s blade by coating the blade with powder wear-resistant coatings using the one-sided gas-flame surfacing technology. The technology of strengthening the cultivator blade using one-sided gas-flame surfacing is applied. As a result, were defined: powder granulation on the thickness of the applied layer; modes and parameters of the one-sided gas-flame surfacing during the formation of composite material coating. Foreign experience of the last decades shows that with the development of gasometric spraying methods it is possible to atomize various materials such as polymers, carbides, metals. These coatings withstand the impact of high thermal loads, shock-abrasive and chemically active environments. Comparison of application methods mentioned above shows that the quality of coatings expressed in the parameters: adhesions, porosity, oxidation levels remain at approximately the same level. However, a comparative analysis of foreign practice has shown that the method of gas-flame surfacing is more technological, more productivity, and the specific costs of the coating are reduced.